Assessing Soil Tolerance Limit for Two Soil Orders Surrounding Sulaimani City - Ahmed, Marwa Abubakr; Sharif Qadir, Kamal (Kurdistan Journal of Applied Research, 2019)
This research was conducted to determined Soil loss tolerance limit (SLTL) which used for soil and water conservation projects and assessing the potential risk of soil erosion. In this study, two different sites were selected including Bakrajo and Qallachwalan were located 9.4 and 23.7 km far from Sulaimani city respectively. The soil orders in the two studied sites were determined through describing the soil profile properties which were known as Vertisols and Mollisols respectively. Each site was divided into 16 sub-sites using the grid point system. The dimension of each site was (2.5*2.5 km). The estimated soil tolerance limit for whole grid points except one grid point at Bakrajo site was equal to 12.5 (Mg/ ha/ yr), while at Qallachwalan in a wide range as 2.5-10 (Mg/ ha/ yr). The mentioned results of soil tolerance limit explained that the Bakrajo site is more resistant to the risk of water erosion compared to Qallachwalan site which was known as a rugged area. Besides the most soil depth of the grid points at Qallachwalan was shallow did not exceed 50 cm. So the Qallachwalan site needs several processes conservation planning than the Bakrajo site which known as more deep and flatty soil.